Understanding the serial mediating effects of career adaptability and career decision-making self-efficacy between parental autonomy support and academic engagement in Chinese secondary vocational students - Jiang, Ruyi; Fan, Ruomeng; Zhang, Yue; Li, Yunxing (Frontiers in Psychology, 2022)
This study investigated new avenues for understanding the association between parental autonomy support and academic engagement among Chinese secondary vocational students based on Self-Determination Theory and Career Construction Theory. We highlighted the mediator role of career adaptability and career decision-making self-efficacy in the relationship between parental autonomy support and academic engagement. Using self-reported data from 1,930 secondary vocational students in a city in Central China, we performed correlation analysis and mediation analysis by using SPSS and Mplus. The results revealed that parental autonomy support was positively associated with students’ academic engagement. Moreover, as an adaptability resource and adapting response, career adaptability and career decision-making self-efficacy played mediating roles between parental autonomy support and academic engagement. These findings offered crucial empirical evidence for understanding the association between parental support and academic engagement among Chinese secondary vocational students. Meanwhile, it also validated the application of Career Construction Theory in a sample of secondary vocational students in China and provided constructive insights for implementing diverse support measures to boost their academic and career development.